2013
DOI: 10.1209/0295-5075/104/47011
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of electron spin lifetime in GaAs crystals: The benefits of dichotomous noise

Abstract: The electron spin relaxation process in n-type GaAs crystals driven by a fluctuating electric field is investigated. Two different sources of fluctuations are considered: (i) a symmetric dichotomous noise and (ii) a Gaussian correlated noise. Monte Carlo numerical simulations show, in both cases, an enhancement of the spin relaxation time by increasing the amplitude of the external noise. Moreover, we find that the electron spin lifetime versus the noise correlation time: (i) increases up to a plateau in the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…A threshold effect is observed, in which an enhancement of the electron spin relaxation length can be maintained for several orders of magnitude of the RT mean switching time, starting from a value equal to 10 times the relaxation characteristic time of the spin system in absence of noise τ 0 . The findings are very similar to those observed for the electron spin lifetimes [79] and a simple argument to explain the numerical results has been extensively discussed in [84].…”
Section: Numerical Results and Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A threshold effect is observed, in which an enhancement of the electron spin relaxation length can be maintained for several orders of magnitude of the RT mean switching time, starting from a value equal to 10 times the relaxation characteristic time of the spin system in absence of noise τ 0 . The findings are very similar to those observed for the electron spin lifetimes [79] and a simple argument to explain the numerical results has been extensively discussed in [84].…”
Section: Numerical Results and Discussionsupporting
confidence: 84%
“…For this reason, the investigation of the spin relaxation processes represents a crucial point in spintronic device design [137,138]. Previous studies of the electron spin relaxation process in GaAs bulks have shown that external fluctuations added to the driving static electric field can affect the spin decoherence process [79,[82][83][84], being this effect critically dependent on the amplitude of both the applied electric field and the external fluctuations, as well as on the noise characteristic times.…”
Section: Spin Polarised Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In the presence of Gaussian correlated fluctuations, the electron ensemble experiences an effective electric field that can be higher or lower than the deterministic one, depending on the value of the noise correlation time, the characteristic memory time of the fluctuations. This affects the electron transport in the semiconductor in such a way that an enhancement or a reduction of the electron spin lifetime, occupation percentage and hot-electron temperature in valley can be obtained [56]. The occurrence of these circumstances depends not only on the ratio between the value of the memory time of the GC noise and the characteristic relaxation time of the spin system, but also on its ratio to both the momentum relaxation time and the momentum redistribution time (characteristic of the electron-electron interaction).…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Previous studies of the electron spin decoherence process in GaAs crystals have revealed that a Gaussian random contribution added to the static driving field can change both the spin depolarisation time and length [ 54,55]. Moreover, recently it has been found that the electron spin lifetime can be changed also when dichotomous random fluctuations are externally added to the driving electric field [56]. In all cases, the external noise can have opposite effects on the electron spin depolarisation process, critically depending on the strength of both the applied voltage and the external noise, as well as on the fluctuation correlation time.…”
Section: Spin Polarised Transportmentioning
confidence: 99%